Recyclable Waste Management System for Tzu Chi Recycling Activities - Liaw, Jing Yin; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
A recycling collection center is an organization that collects recycled materials for the purpose of resale or conversion to other products. these centers are usually run by companies or individuals. However, there are several issues encountered in managing activities at recycling center including manual entry for data storage, manpower task management, and lack of a systematic system to support recycling activities. To support recycling activities at the case study location, Tzu Chi, a system was developed for administrators, volunteers, and drivers at this recycling center. The system allows users to keep records of recycled waste collected in a database. Administrators can retrieve records to generate reports, create payment invoices, and control task management. The system was developed with a prototype-based methodology and system analysis was conducted in an object -oriented approach. This system was developed with MAMP, PHP, and Sublime. Through this system, users at the recycling center can manage their recycling activities more efficiently especially the management of their operational data. The system is also expected to keep all records of recycling waste, the activities, and other related transaction record in the database.